Mechanically assisted cough strategies: user perspectives and cough flows in children with neurodisability - Brit Hov; Tiina Andersen; Michel Toussaint; Ingvild B. Mikalsen; Maria Vollsæter; Cathrine Brunborg; Mathea Hovde; Vegard Hovland (ERJ Open Research, 2024)
Background Mechanical insufflation–exsufflation (MI-E) is used to augment cough in children with neurodisability. We aimed to determine the user comfort and cough flows during three MI-E strategies, and to predict factors associated with improved comfort and cough flows. Methods This multicentre, crossover trial was done at four regional hospitals in Norway. Children with neurodisability using MI-E long term via mask were enrolled. In randomised order, they tested three MI-E setting strategies (in-/exsufflation pressure (cmH2O)/in (In)- versus exsufflation (Ex) time): 1) “A-symmetric” (±50/In=Ex); 2) “B-asymmetric” (+25– +30)/−40, In>Ex); and 3) “C-personalised”, as set by their therapist. The primary outcomes were user-reported comfort on a visual analogue scale (VAS) (0=maximum comfort) and peak cough flows (PCF) (L·min−1) measured by a pneumotachograph in the MI-E circuit. Results We recruited 74 children median (IQR) age 8.1 (4.4–13.8) years, range 0.6–17.9, and analysed 218 MI-E sequences. The mean±sd VAS comfort scores were 4.7±2.96, 2.9±2.44 and 3.2±2.46 for strategies A, B and C, respectively (A versus B and C, p<0.001). The mean±sd PCF registered during strategies A, B and C were 203±46.87, 166±46.05 and 171±49.74 L·min−1, respectively (A versus B and C, p<0.001). Using low inspiratory flow predicted improved comfort. Age and unassisted cough flows increased exsufflation flows. Conclusions An asymmetric or personalised MI-E strategy resulted in better comfort scores, but lower PCF than a symmetric approach utilising high pressures. All three strategies generated cough flows above therapeutic thresholds and were rated as slightly to moderately uncomfortable.